2008
DOI: 10.1111/j.1745-4565.2008.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Frozen “Edamame” (Vegetable Soybean)

Abstract: This study compared the microbiological quality of frozen “edamame” to other varieties of frozen beans sold in Virginia. Furthermore, the reduction of microorganisms during experimental edamame processing was investigated. Commercial frozen in‐pod and shelled edamame had aerobic mesophiles at 3.4 and 3.1 log cfu/g, yeasts and molds at 2.3 and 2.1 log cfu/g, and some contained low levels of Escherichia coli and enterotoxigenic Bacillus spp. Salmonellae were not found; however, 5% edamame and 4% frozen beans in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
7
1
1
Order By: Relevance
“…One study on frozen edamame showed that commercial frozen in-pod and shelled edamame had aerobic mesophiles at 3.4 and 3.1 log cfu/g, yeasts and molds at 2.3 and 2.1 log cfu/g, and some contained low levels of Escherichia coli and enterotoxigenic Bacillus spp [25]. Currently, there is no comprehensive information on blanched and cold-stored edamame.…”
Section: Introductionmentioning
confidence: 99%
“…One study on frozen edamame showed that commercial frozen in-pod and shelled edamame had aerobic mesophiles at 3.4 and 3.1 log cfu/g, yeasts and molds at 2.3 and 2.1 log cfu/g, and some contained low levels of Escherichia coli and enterotoxigenic Bacillus spp [25]. Currently, there is no comprehensive information on blanched and cold-stored edamame.…”
Section: Introductionmentioning
confidence: 99%
“…The consumption difference between soybeans and edamame is in the stage of maturity when the beans are harvested. Edamame beans are harvested before full maturity when bean pods are green and just before turning to yellow (Basavaraja, Naidu, & Salimath, 2005;Hu et al, 2006;Pao et al, 2008). Similarly to dried soybeans, the seeds of edamame are characterized by high nutritional and medicinal value (Konovsky, Lumpkin, & MeClary, 1994 (Sirisomboon, Pornchaloempong, & Romphophak, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Long term storage consists in maintaining pods or beans in frozen form after blanching. The cold storage of fresh beans and pods proved successful in many countries including Australia (James, 2007), United States (Wszelaki et al, 2005;Pao et al, 2008;Carson et al, 2011;Jiang et al, 2018), Taiwan (Shanlnugasundaram et al, 1992), India (Kumar et al, 2011), Thailand (Sarutayophat, 2012), China (Li et al, 2013;Zhang et al, 2017), Argentina (Benavidez et al, 2010) and Latvian (Zeipiņa et al, 2017). Most authors reported on blanching as pre-treatment before cold storage, with various target advantages.…”
Section: Harvest and Post-harvest Handlingmentioning
confidence: 99%
“…Most authors reported on blanching as pre-treatment before cold storage, with various target advantages. Pao et al (2008) investigated the effect of frozen edamame on its microbiological quality and indicated that blanching treatment at 98°C for about 60 s eliminates yeasts, molds, coliforms as well as infectious species Escherichia coli and Listeria spp. Moreover, Xu et al (2012) demonstrated that blanching for 2.5 min or more at 100°C increases the green color intensity of edamame beans, Source: Chadha and Oluoch (2004). reduces the activities of yeasts, molds, total bacteria and 98% of peroxidase activities, thus alleviating the toxic effect of peroxide accumulation.…”
Section: Harvest and Post-harvest Handlingmentioning
confidence: 99%